Reading comprehension performance of elementary and senior high school students - de Oliveira, Adriana Marques [UNESP]; Santos, Jair Lício Ferreira; Capellini, Simone Aparecida [UNESP] (Frontiers, 2023)
Introduction: In Brazil, reading has been widely discussed, mainly due to the published results of national and international performance exams of Brazilian schoolchildren. Learning to read is therefore a continuous process, and the ability to make inferences while reading a text develops with age. The textual complexity involving the syntactic structuring, vocabulary and types of text progressively increases from the initial years of elementary school to high school students, also increasing the cognitive demand of the students; this occurs in parallel to their development and school advancement, which allows improvements in their teaching/learning processes. Based on the above, the following questions were raised: (1) How is the semantic process of reading established among elementary school students in elementary school (cycle II) and high school? Aim: to characterize the performance of elementary and senior high school students on semantic process tests from the Brazilian adaptation of the evaluation of reading processes (PROLEC-SE-R). Methods: A total of 436 students of both sexes, aged between 11 and 18 years, participated. They were evaluated with Assessment of Reading Processes-PROLEC-SE-R. Results and discussion: The results indicated that the semantic process was equally established among high school students, with a higher average performance compared with that of elementary school students. Among elementary school students, there was progression in the average correct answers with advancement in schooling. In the two levels of education, narrative texts allowed a greater number of correct answers, followed by multiple-choice and literal questions. The PROLEC-SE-R semantic process tests proved to be effective for assessing reading comprehension in elementary and high school students and reflected the Brazilian reality with regard to the gaps and weaknesses in the educational system.
Keywords: adolescence; assessment; education in Brazil; high school; middle school; reading; reading comprehension